Experiences of mothers with preterm babies on support services in Neonatal Intensive Care Unit of a mission hospital in Ghana - Dominic Bachegejoa Apedani; Amankwah Koduah; Andrews Adjei Druye; Nancy Innocentia Ebu (Elsevier, 2021)
Background: Hospitalisation of a preterm baby presents significant burden to parents, especially mothers. However, little evidence on supportive services to improve self-efficacy for mothers on caring for their preterm babies exist. This study explored the experiences of mothers of preterm babies regarding the support services they received at the Neonatal Intensive Care Unit (NICU) of a mission hospital in Ghana. Methodology: The study utilised the explorative descriptive qualitative case study design with purposive sampling of mothers of preterm babies admitted in the NICU. In-depth interviews were conducted on 16 mothers of preterm babies using a semi-structured interview guide until data saturation was reached. The interviews were audio taped, transcribed and analysed using thematic content analysis. Findings: The findings showed that mothers generally received some form of logistical support (sleeping room, mattresses, bath rooms and toilets), psychosocial support services (counselling, peer support, kangaroo mother care) and health education from various health professionals. However, these support services were not adequately available to meet their needs. Conclusion: Mothers of preterm babies experienced less support during hospitalisation of their babies in the NICU of a mission hospital in Ghana. The mothers expressed the desire that health professionals in neonatal care settings should offer physical and psychosocial support to parents of preterm infants to build their capacity in caring for the babies. There was the need for a multidisciplinary approach to organising support services at the NICU.